THE USE OF COLLABORATIVE METHOD IN TEACHING WRITING USING SHORT STORIES - Noviana Ikhsana Rambe; Irmala Sukendra; Syifa Fadhilah Hamid (English Language Education Department, Faculty of Teacher Training and Education, Syekh-Yusuf Islamic University (PBI FKIP UNIS), 2023)
Writing is the ability to articulate and express ideas or emotions that arise in the mind in the form of words, phrases, and paragraphs. Throughout the writing process, some students have expressed that learning to write feels tedious and unimportant to them. When teaching writing, there are numerous strategies that must be employed to promote written communication among students. Collaborative writing is a strategy that can be employed in pairs or groups and has been proven to be effective in addressing students' writing challenges. A short story is a type of concise fiction, considering the events portrayed, the content of the story, the number of characters, and the word count used. This research aims to determine the influence of the collaborative method using short stories on the improvement of students' writing skills in one of the the SMK PGRI in Tangerang Kota. The variables in this research are the collaborative short story method and writing skills. This research falls under the Quasi-Experimental category and employs a quantitative approach. In this study data was collected from a sample of 70 students. The research hypothesis was tested using the Wilcoxon test, and the conclusion drawn is that there is a influence of the collaborative short story method on students' writing skills. Key Words: Collaborative Method, Short Story, Teaching Writing